Verification of the Relationship between Redox Regulation of Thioredoxin Target Proteins and Their Proximity to Thylakoid Membranes - Yuka Fukushi; Yuichi Yokochi; Ken-ichi Wakabayashi; Keisuke Yoshida; Toru Hisabori (Antioxidants, 2022)
Thioredoxin (Trx) is a key protein of the redox regulation system in chloroplasts, where it modulates various enzyme activities. Upon light irradiation, Trx reduces the disulfide bonds of Trx target proteins (thereby turning on their activities) using reducing equivalents obtained from the photosynthetic electron transport chain. This reduction process involves a differential response, i.e., some Trx target proteins in the stroma respond slowly to the change in redox condition caused by light/dark changes, while the ATP synthase γ subunit (CF1-γ) located on the surface of thylakoid membrane responds with high sensitivity. The factors that determine this difference in redox kinetics are not yet known, although here, we hypothesize that it is due to each protein’s localization in the chloroplast, i.e., the reducing equivalents generated under light conditions can be transferred more efficiently to the proteins on thylakoid membrane than to stromal proteins. To explore this possibility, we anchored SBPase, one of the stromal Trx target proteins, to the thylakoid membrane in Arabidopsis thaliana. Analyses of the redox behaviors of the anchored and unanchored proteins showed no significant difference in their reduction kinetics, implying that protein sensitivity to redox regulation is determined by other factors.